Climate-Smart Agriculture Manual for Agriculture Education in Zimbabwe - Huyer, Sophia; Nyasimi, Mary (Climate Technology Centre and Network, 2017)
This chapter addresses the critical links of gender with climate change and agriculture. In Zimbabwe and the rest of the developing world, both women and men are smallholders, yet the role that women play is often unrecognised. Globally, women make up 43% of the agricultural labour force, and in Zimbabwe they provide 70% of agricultural labour. Women face structural barriers that create gender gaps and inequalities. Women farmers in southern Africa, as a result, face barriers in adopting CSA practices, including unequal access to credit, technology and agricultural inputs as well as capacity-building. The changing climate is poised to exacerbate these inequalities unless measures are taken to address them. This chapter demonstrates that climate-smart agriculture practices and policies will need to take these barriers into account and develop solutions to address them. Highlighted CSA case studies not only improve food security and increase incomes, but also benefit women and reduce gender barriers. Finally, the chapter emphasises the importance of developing and implementing gender-responsive climate change and agricultural practices, and of mainstreaming gender into academic curricula.